1997
DOI: 10.1038/sj.onc.1201037
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localisation of the ataxia-telangiectasia (ATM) gene product and discrimination between mutated and normal forms

Abstract: The recently cloned gene (ATM) mutated in the human genetic disorder ataxia-telangiectasia (A-T) is involved in DNA damage response at dierent cell cycle checkpoints and also appears to have a wider role in signal transduction. Antibodies prepared against peptides from the predicted protein sequence detected a * 350 kDa protein corresponding to the open reading frame, which was absent in 13/23 A-T homozygotes. Subcellular fractionation, immunoelectronmicroscopy and immunouorescence showed that the ATM protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 38 publications
(61 reference statements)
9
129
1
Order By: Relevance
“…Immunostaining using anti-ATM and anti-FLAG antibodies localized the recombinant ATM predominantly in the nucleus, and a minor fraction remaining in the cytoplasm. This localization is similar to that of endogenous ATM in various cell types, as recently reported by several laboratories (Brown et al, 1997;Chen and Lee, 1996;Lakin et al, 1996;Watters et al, 1997). The cytoplasmic fraction of ATM appears to be microsomal (Brown et al, 1997;Watters et al, 1997), and immunoelectronmicroscopy recently performed by Watters et al (1997) showed association of the protein with certain vesicular structures.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Immunostaining using anti-ATM and anti-FLAG antibodies localized the recombinant ATM predominantly in the nucleus, and a minor fraction remaining in the cytoplasm. This localization is similar to that of endogenous ATM in various cell types, as recently reported by several laboratories (Brown et al, 1997;Chen and Lee, 1996;Lakin et al, 1996;Watters et al, 1997). The cytoplasmic fraction of ATM appears to be microsomal (Brown et al, 1997;Watters et al, 1997), and immunoelectronmicroscopy recently performed by Watters et al (1997) showed association of the protein with certain vesicular structures.…”
Section: Discussionsupporting
confidence: 85%
“…Endogenous ATM is predominantly nuclear (Brown et al, 1997;Chen and Lee, 1996;Lakin et al, 1996;Watters et al, 1997). Immunostaining using anti-ATM and anti-FLAG antibodies was used to localize the endogenous protein in immortalized normal fibroblasts, and the recombinant protein produced in AT22IJE-T cells.…”
Section: Localization Of Recombinant Atm By Immunostainingmentioning
confidence: 99%
“…This is consistent with the observation of endogenous ATM protein in normal fibroblast cells detected with immunofluorescent histochemistry. 7 A prior report emphasized that the ATM was distributed within the cytoplasm of the Purkinje cells, but not within the nuclei. 49 This discrepancy may stem from the differences within species or from different techniques used to stain the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analyses have revealed that the ATM gene product is a polypeptide around 350 kDa that localizes to the nucleus and within vesicular structures in the cytoplasm. [5][6][7][8] The exact role of the ATM protein is not yet known. However, based on the pleiotropic phenotype of AT and its close relationship to a family of phosphatidylinositol (PI) 3-kinases, it is linked to signal transduction, cell cycle control, DNA repair-related mechanisms, and resistance to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Immunostaining using anti-ATM (3E8) and anti-FLAG (FLAG M2) antibodies was used to localize the FLAG-ATM protein produced 48 h postinfection with the HGC-ATM amplicon vector. The results (Figure 3) indicate that the vector-expressed FLAG-ATM was also localized in the nucleus.…”
Section: Localization Of Flag-atm By Immunofluorescencementioning
confidence: 99%